Quality Program for NI-43101 compliance in exploration activities for anthracite coal project - Carrasco Rodríguez, Marco David (2021)
Quality program is important for achieving the objectives of mining projects. They consist of the quality management plan, quality management and assurance (QA) and quality control (QC). They are a tool implemented by the mining companies in order to have valid information that allows the elaboration of resource mineral estimation and reserve mineral estimation studies. The International Standard NI 43101 contains the guidelines for the elaboration of the reports to stock exchanges and bankable feasibility study. The content of the standard is applied in the elaboration of the Quality Program and thus it can be implemented during the activities of a project such as field geology, drilling campaigns, geotechnical, hydrogeological, hydrological studies, topography, security, environmental evaluations and water quality studies. In this sense, the Quality Program requires highly specialized staff and is part of the policies and procedures of mining companies.